Adalimumab treatment optimization for psoriasis: Results of a long‐term phase 2/3 Japanese study. Issue 11 (29th June 2015) - Asahina, Akihiko; Ohtsuki, Mamitaro; Etoh, Takafumi; Gu, Yihua; Okun, Martin M.; Teixeira, Henrique D.; Yamaguchi, Yuji; Nakagawa, Hidemi
Abstract The tumor necrosis factor‐α inhibitor, adalimumab, is approved to treat moderate‐to‐severe plaque psoriasis (40 mg every‐other‐week or 80 mg every‐other‐week following inadequate response at 40 mg in Japan). This open‐label extension (OLE) trial evaluated the optimal adalimumab dose for long‐term efficacy and safety in Japanese patients with moderate‐to‐severe plaque psoriasis following a prior 24‐week, phase 2/3, randomized, double‐blind study. Of the 169 patients from the phase 2/3 trial, 147 entered the OLE on 40 mg (n = 89) or 80 mg (n = 58) adalimumab every‐other‐week. Patients on 40 mg with Psoriasis Area and Severity Index (PASI) of less than 50 could escalate to 80 mg. At week 52 (28 of OLE), patients entering the OLE on 80 mg were reduced to 40 mg, with the option to re‐escalate. For patients entering the OLE on 40 mg, final PASI 50/75/90 response rates were 85.1%/73.3%/60.4%, respectively, including effects of dose escalation. Among patients whose dose was escalated, final PASI 50/75/90 response rates were 70.0%/53.3%/36.7%, respectively. For patients entering the OLE on 80 mg, final PASI 50/75/90 response rates were 92.5%/84.9%/73.6%, respectively, including effects of dose re‐escalation. Overall incidence rates of adverse events (AE) and injection‐site reaction AE declined over time; rates for serious AE and infections were generally stable. Clinically meaningful efficacy of adalimumab was sustained to 4 years. Dose escalation to 80 mg every‐other‐week for patients with suboptimal response to 40 mg every‐other‐week, and dose reduction to 40 mg every‐other‐week for patients satisfactorily controlled on 80 mg every‐other‐week, are viable strategies for adalimumab optimization.